Gut-thyroid axis and celiac disease - Aaron Lerner; Patricia Jeremias; Torsten Matthias (Endocrine Connections, 2017)
Autoimmune thyroiditis has an increased prevalence in patients with celiac disease and vice versa. The objective of the current review is to highlight the epidemiological, clinical, serological, pathological, pathophysiological, hormonal, genetic and immunological factors shared between the two entities. They might represent the two ends of the gut-thyroid axis where the cross-talks’ pathways are still unravelled. New observations are reviewed, highlighting some gut-thyroid interrelated pathways that potentially might lead to new therapeutic strategies.